Distribution, morphological characterization and pathogenicity of Fusarium sacchari associated with pokkah boeng disease of sugarcane in Peninsular Malaysia - Mohamed Sidique, Siti Nordahliawate; Mohd Zainuddin, Nur Ain Izzati; Abdul Razak, Azmi; Salleh, Baharuddin (Universiti Putra Malaysia, 2008)
Pokkah boeng disease on sugarcane has been recorded in almost all countries where sugarcane is growl)commercially. The objectives of this study were to survey the distribution of Fusarium sacchari associated with pokkah boeng disease throughout Peninsular Malaysia, to isolate and identify the causal organisms by using morphological characteristics, and to ascertain the pathogenicity of F. sacchari based on Koch's postulates. A total of 58 strains of F. sacchari were obtained throughout sugarcane plantations, small holders and household compounds within seven states i.e. Kedah, Perlis, Penang, Kelantan, Terengganu, Pahang and Johor in Peninsular Malaysia. The highest number of F: sacchari strains was obtained from Kedah (48%), followed by Perlis (25%), Penang (3%), Pahang (3%), Kelantan (5%), Terengganu (8%) and Johor (8%). For identification of F. sacchari, carnation leaves agar (CLA) and potato dextrose agar (PDA) media were used with emphasis for characterizations of colony features, growth rates, shapes and sizes of macroconidia and microconidia, conidiogeneous cells and chlamydospores. In plant house pathogenicity tests, healthy seedlings of sugarcane cultivar PS-81-362 were inoculated by injection and soaking techniques with conidial suspension (2x106 conidia/ml) of selected strains of F. sacchari, F. proliferatum and F. subglutinans. All strains of F. sacchari tested were pathogenic to sugarcane plants with disease severity index (DSI) varying from 0.3 to 5.0 (0 for no visible symptoms and 5 for plants with symptoms of twisted, wrinkled and shortened leaves or death). There were no significant (p>0.05) difference in DSI caused by strains of F. sacchari on variety PS-81-362 for both inoculation techniques, although they were significantly different compared with the control. This knowledge would be invaluable in developing our understanding on the interaction between F. sacchari with the host plants.